The correlation between p16 expression and INK4a locus mutation with grades and stages in oral squamous cell carcinoma - Soudabeh Sargolzaei; Sareh Farhadi; Bahram Kazemi; Mojgan Bandehpour; Mohammad Javad Kharazifard (Wolters Kluwer Medknow Publications, 2014)
Objective: p16INK4a is a tumor suppressor gene playing a critical role. Researches have indicated the gene to be altered in oral squamous cell carcinoma. Present studies have tried to assess the correlation between p16INK4a expression and INK4a locus mutation in relation to grades and stages of this tumor. Materials and Methods: Expression of p16INK4a was studied immunohistochemically in 58 oral squamous sell carcinoma samples and INK4a locus mutation was determined by polymerase chain reaction (PCR) and conformation sensitive gel electrophoresis (CSGE). Results: Expression of p16INK4a was higher in stage1 compared to stage 2, 3, and 4 (P = 0.234). The difference was not significant in grade 1, 2, and 3 (P = 0.671). The average values of total score (TS) were significantly higher in stage1 compared to stage 2, 3, and 4 (P = 0.035). The average values of complete score (CS) were higher in stage 1 compared to stage 2, 3, and 4 (P = 0.061). The research did not show a significant correlation between lymph node involvement and p16INK4a expression (P = 0.491). It seems that 5.1% (3/58) of samples have mutation in INK4a locus. Conclusion: Loss of p16INK4a expression occurred in initial stages of oral squamous cell carcinoma. Evaluation of TS and CS for p16INK4a might be a useful clinical indicator concerning the tumor. However, gene mutation is believed to have minor rate of genetic alteration in carcinogenesis.